Telaah Religiusitas pada Novel â€œJangir Baliâ€ Karya Nur Sutan Iskandar - Tu Jahro, Siti Fatimah (Holistik: Journal for Islamic Social Sciences, 2019)
Literature is an afterthought of a picture of life. Literature always expresses a broad, deep life and also human life which is full of challenges and struggles. Literature also contains stories of humanity, gestures of faith, love, honesty and reality. One of these literary works is a novel. A novel can be analyzed by various studies or studies, such as the study of feminism, the study of semiotics, the study of post-colonial, the study of ideology-philosophy, and the study of values. This paper aims to examine the novel based on religious values. This research is a descriptive qualitative research. Data sources were obtained from the novel "Jangir Bali". Data collection through observation of novels. Data analysis uses descriptive analysis. Based on the analysis of the data that has been conducted, it can be concluded that the religious value in the novel "Jangir Bali" is to teach people to have faith, worship, be patient, do everything sincerely, always be grateful, always pray, and be kind to others